Faktor-Faktor yang Mempengaruhi Minat Berwirausaha Mahasiswa (Studi pada Mahasiswa Fakultas Ekonomi dan Sosial Universitas Jenderal Achmad Yani Yogyakarta) - Krisna Mutiara Wati (HOME, 2020)
This study aims to determine the factors that influence student interest in entrepreneurship. Students who were the object of research were students of the Faculty of Economics and Social Yogyakarta Unjani who had attended a seminar on business or entrepreneurship. This research was conducted by survey method using a questionnaire. Data were analyzed with the help of the SPSS program. The results of the study are that there is a significant effect of internal factors on entrepreneurial interest, no significant effect of external factors on entrepreneurial interest, and there is a significant effect simultaneously or jointly on internal factors and external factors on entrepreneurial interest.The most influential internal factor according to students is the dream factor, while for external factors the support or enthusiasm factor of the family has the highest influence on entrepreneurial interest.